A Complex Consulting Architecture for Sustainable Business Model Transformation in Small and Medium-Sized Enterprises under Global Economic Volatility - Prof. Claudia H. Fairchild (Emerging Frontiers Library for The American Journal of Social Science and Education Innovations, 2025)
Small and medium-sized enterprises (SMEs) constitute the structural backbone of most national economies, yet they are also the most vulnerable to economic shocks, regulatory complexity, technological disruption, and institutional instability. Over the past two decades, globalization, digitalization, geopolitical turbulence, and sustainability pressures have fundamentally reshaped the strategic environment in which SMEs operate. Traditional business consulting models, historically derived from large corporate contexts, increasingly fail to address the distinctive cognitive, organizational, financial, and institutional constraints that characterize SMEs. This article develops a comprehensive theoretical and methodological framework for a complex model of business consulting specifically designed for SMEs, integrating sustainability, social entrepreneurship, innovation, crisis resilience, and institutional embeddedness into a unified analytical architecture. The Discussion advances a new theoretical position in which consulting is understood as an enabling infrastructure for SME resilience and sustainable value creation. It challenges dominant efficiency-based consulting paradigms and demonstrates how complex consulting models are better aligned with the uncertainty, informality, and moral economy of SMEs in emerging and volatile markets. The article concludes by outlining the implications of this framework for policymakers, practitioners, and scholars, emphasizing that SME consulting must be reimagined as a long-term co-evolutionary partnership rather than a short-term technical intervention.